Clinical effects of two different doses of duloxetine compared to conventional analgesic therapy in patients with osteoarthritis knee - Choudhury, Arpita; Bhattacharya, Dipasri; Biswas, Rajasree; Saroha, Swati; Chakraborty, Nitisha; Roy, Samrat (Asian Journal of Medical Sciences, 2021)
Background: Pain is the leading symptom of knee osteoarthritis (OA) leading to significant morbidity and decreased quality of life. Duloxetine, a selective serotonin norepinephrine reuptake inhibitor, has been demonstrated to have a centrally acting analgesic effect. Aims and Objectives: To evaluate the efficacy and safety of two different doses of duloxetine and compare with conventional pharmacotherapy in treatment of chronic pain due to osteoarthritis of knee. Materials and Methods: 90 patients with symptomatic knee OA were randomly divided into 3 groups to receive duloxetine 40 mg & 3g paracetamol/day (Group A), duloxetine 20 mg & 3g paracetamol/day (Group B) and paracetamol 3gm/day (Group C). Patients were followed up for 6 months to assess pain relief and functional improvement. Visual Analogue Scale (VAS) for assessing pain intensity and Western Ontario and McMaster Universities Arthritis Index (WOMAC) questionnaire physical function subscale for assessing physical function were used. Results: Reduction in VAS score from baseline was significantly high in groups A and B as compared to C at 1 month, 3 months and 6 months. Reduction in WOMAC score from baseline were also significantly high in groups A and B as compared to C at 1 month, 3 month and 6 months. Adverse effects in Group A were significantly high as compared to group B and C. Patients discontinuing due to adverse effects were significantly high in group A. Conclusion: Lower dose of duloxetine is associated with significant pain reduction and improved function with lesser adverse effects in patients with pain due to knee OA.